Phenylalanine metabolism regulates reproduction and parasite melanization in the malaria mosquito. - Silke Fuchs (Public Library of Science (PLoS), 2014)
The blood meal of the female malaria mosquito is a pre-requisite to egg production and also represents the transmission route for the malaria parasite. The proper and rapid assimilation of proteins and nutrients in the blood meal creates a significant metabolic challenge for the mosquito. To better understand this process we generated a global profile of metabolite changes in response to blood meal of Anopheles gambiae, using Gas Chromatography-Mass Spectrometry (GC-MS). To disrupt a key pathway of amino acid metabolism we silenced the gene phenylalanine hydroxylase (PAH) involved in the conversion of the amino acid phenylalanine into tyrosine. We observed increased levels of phenylalanine and the potentially toxic metabolites phenylpyruvate and phenyllactate as well as a reduction in the amount of tyrosine available for melanin synthesis. This in turn resulted in a significant impairment of the melanotic encapsulation response against the rodent malaria parasite Plasmodium berghei. Furthermore silencing of PAH resulted in a significant impairment of mosquito fertility associated with reduction of laid eggs, retarded vitellogenesis and impaired melanisation of the chorion. Carbidopa, an inhibitor of the downstream enzyme DOPA decarboxylase that coverts DOPA into dopamine, produced similar effects on egg melanization and hatching rate suggesting that egg chorion maturation is mainly regulated via dopamine. This study sheds new light on the role of amino acid metabolism in regulating reproduction and immunity.